The Role of the Job Demands & Job Resources Model (JD-R Model) on Turnover Intention with Employee Engagement and Job Satisfaction as Mediating Variables - Rehabeam Rehabeam; Unggul Kustiawan (International Journal Labs, 2025)
The purpose of this study is to further investigated the role of job demand & job resources model (JD-R Model) on employee turnover intention with employee engagement and job satisfaction as mediating variables. This quantitative study using the Structural Equation Model (SEM) method began in early 2024. The population of this study is focusing on nurses who work in type B private hospitals in Tangerang area. Research data was collected by distributing questionnaires online using google form which resulted in a total of 153 respondents. The findings of this research show that there is an indirect influence between the JD-R Model on turnover intention through the mediating role of job satisfaction and employee engagement. The influence of job satisfaction and employee engagement is an important factor in reducing the low turnover intention rate of nurses in hospitals. This study provides managerial implications for organizations operating in the healthcare industry such as hospitals, hospital management to empower nurses properly, because nurses have a very vital role in the running of services in hospitals. Nurses who have high engagement with the hospital will provide maximum contributions in improving the hospital's performance